Teachers ' Awareness of Teaching Professional Code of Ethics, Acts and Regulations in Mkuranga District, Tanzania - Boniface, Raymond Mwemezi; Ngalawa, Christina Francis (Papers in Education and Development, 2021)
This paper explores public primary school teachers ' awareness of the teaching professional code of ethics, acts and regulations in Mkuranga District in Tanzania. Data from 50 teachers were collected using semi-structured interviews and questionnaires and then subjected to content analysis and descriptive statistics. The findings indicate that most teachers (about 75% with disciplinary cases and 50% without disciplinary cases) were not aware of teachers ' professional code of ethics; 75% of teachers sampled had been introduced to teachers ' professional code of ethics during their professional training in colleges and universities; 70% of sampled teachers had not have an opportunity to update their awareness of these ethics. Further, heads of schools possessed little awareness of the acts and regulations which empower them to deal with teachers ' ethics. Keywords: ethical acts, professional code of ethics, regulations, teachers ' unethical practices